Analysis on the effect of salinity in underwater wireless optical communication. Issue 3 (15th March 2020) - Kumar, Sanjay; Prince, Shanthi; Venkata Aravind, Jinka; Kumar G, Santosh
Abstract: This article deals with the effect of salinity variation on underwater wireless optical communication (UWOC). Effect of different concentration of salt on underwater optical communication has been carried out experimentally in terms of received power at different link lengths. Based on the analysis of experimental data, a mathematical model has been proposed to describe the saline water channel. A simulation study is performed for different data rates and link lengths. It is seen that with increased salinity the attenuation is higher and the UWOC system performance degrades with higher data rate and increased link length.